Taxation and Economic Stability - Salera, Virgil (Quarterly Journal of Economics, 1943)
Journal Article Taxation and Economic Stability Get access Virgil Salera Virgil Salera Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 57, Issue 2, February 1943, Pages 323–325, https://doi.org/10.2307/1882757 Published: 01 February 1943